ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PRODUK, KUALITAS LAYANAN, HARGA, LOKASIâ€ (Studi Kasus Pada Waroeng Bamboe di Tembalang-Semarang) - Prasetyo, Tri Adhy; Djastuti, Indi (Diponegoro Journal of Management, 2015)
A venture business especially in the field of culinary must issue the products should adapt to the needs and desires of consumers. So the products can compete in the market ,making consumers have many choices of products before making a decision to buy a product that is offered. If consumers have a choice between making a purchase and do not make a purchase or option to use the time, the consumer is in a position to take a decision. Consumer decision may be influenced by several variables, this study analyzed the quality of products, quality of service, price, and location. The population in this study is that consumers who buy a product that is offered at Waroeng Bamboo Tembalang, Semarang. The sample in this study was 100 consumers.The sampling technique in this study was done by using Non Probability Sampling with incidental sampling technique, the sampling technique by coincidence, that anyone who happened to meet with researchers and considered fit to be the source of the data will be sampled this study. Methods of data collection using kuesioner. Teknik analysis used is quantitative data analysis methods.Analyss results using multiple regression showed that : Product quality proven influence on purchasing decisions. Quality of Service proven influence on purchasing decisions. Price shown to influence the purchasing decision, and location proved to influence the purchase decision.